Megakaryocytes as immune cells - Cunin, Pierre (J Leukoc Biol, 2019)
Platelets play well-recognized roles in inflammation, but their cell of origin – the megakaryocyte – is not typically considered an immune lineage. Megakaryocytes are large polyploid cells most commonly identified in bone marrow. Egress via sinusoids enables migration to the pulmonary capillary bed, where elaboration of platelets can continue. Beyond receptors involved in hemostasis and thrombosis, megakaryocytes express receptors that confer immune sensing capacity, including Toll like receptors and Fc γ receptors. They control the proliferation of hematopoietic cells, facilitate neutrophil egress from marrow, possess the capacity to cross-present antigen, and can promote systemic inflammation through microparticles rich in interleukin 1. Megakaryocytes internalize other hematopoietic lineages, especially neutrophils, in an intriguing cell-in-cell interaction termed emperipolesis. Together, these observations implicate megakaryocytes as direct participants in inflammation and immunity.